Secure attachment may foster psychological momentum through building enduring happiness: insights from an exploratory cross-sectional study involving regular exercisers - Briki, Walid; Markman, Keith D. (Frontiers in Psychology, 2025)
Past research has shown that secure attachment promotes hedonic or fluctuating forms of happiness by enhancing perceptions of goal progress. The present study extends this work by examining authentic-durable happiness—a more stable, peace-oriented form of well-being—and by positioning psychological momentum (PM) as an experiential construct of exploration. Regular exercisers (N = 511) completed online questionnaires assessing secure attachment, authentic-durable happiness, and PM over the previous four weeks. To clarify the interrelationships among these constructs, we tested two competing structural equation models. Model 1, grounded in a hedonic perspective, specified PM as a mediator between secure attachment and authentic-durable happiness. Model 2, informed by eudaimonic and self-determination theory perspectives, specified authentic-durable happiness as a mediator between secure attachment and PM. Results indicated stronger support for Model 2: Authentic-durable happiness partially mediated the relationship between secure attachment and PM. These findings highlight authentic-durable happiness as a key psychological resource linking secure attachment to sustained engagement. By contrasting hedonic and eudaimonic perspectives, the study advances attachment theory beyond fluctuating happiness and provides preliminary evidence that secure attachment may foster enduring well-being, which in turn may energize perceptions of PM. Overall, this work introduces PM as a phenomenological manifestation of exploration and underscores the value of examining both transient and durable happiness in understanding the motivational impact of secure attachment.